Efektifitas Wire Rope Sebagai Perkuatan padaDaerah Momen Negatif Balok Beton Bertulang Tampang T - Yanuar Haryanto (Jenderal Soedirman University, 2011)
The loss due to collapsing structure includes not only materialsbutalso take lives. In thecase of structure function changing that may cause increasing loads, it is required to put efforts instrengtheningthe structure elements in order to increase the capacity and hence to avoid the possibility of collapsing. The objective of this research was to study thebehavior of T-sectional reinforced concrete beamstrengthenedin the negative momentregionwithwire rope and mortar composite. The test was carried out to three T-sectional beams: without wire rope reinforcement (BK), with 2 wire rope reinforcements (BP1), and with 4 wirerope (BP2) reinforcements. The type of wire rope was Independent Wire Rope Core (IWRC) with10 mm diameter. The testing method used was two points static loading with flens positions below (the flens part experienced tensile stress). Results showed that the maximum load carryingcapacity of BP1 and BP2 specimens increased by ratios of 1.59 and 2.03 to the BK specimen respectively. However, the increase was achievedafter the development and propagation of highcracking. Ductility of BP1 and BP2 specimens decreased by ratios of 0.62 and 0.36 to the BK specimen respectively. The initial stiffness of BP1 and BP2 increased byratios of 1.09 and 1.08 to the BK specimen respectively.The effective stiffness ofBP1 and BP2 specimensdecreased by ratios of 0.88 and 0.92 to the BK specimenrespectively. Stress occurred in the wire rope based on the analysis results of Response-2000 and the layer method have not reached 50% ofthe ultimate stress resulted from the preliminary test. In general, unless improvement was given to the stiffness characteristics of thewire rope, its contribution would not become optimum.